(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to study the role of strategic alliances between the banking sector and the telecommunications sector and the banks ’achievement of marketing innovation, within the conditions of the economic and technological blockade imposed on Syria. To achieve this, two main hypotheses were formulated, and the researcher used the questionnaire method to collect the data that were analyzed using statistical tests, the most important of which are: The One-Sample T. test, the Pearson Correlation test, and the simple regression analysis. The researcher reached several results, the most important of which are: A good strategic alliance between the telecommunications sector and the studied banks, and it takes a form of cooperation between non-competing organizations to achieve common goals that serve both parties in a way that reflects positively on the wheel of economic development in Syria, whether this alliance is to enter new markets or in the field of technology, and there is also a Good positive relationship between the strategic alliances between the banking sector and the Syrian telecommunications sector and achieving marketing innovation in these banks, whether these strategic alliances are to enter new markets or in the field of technology.